TRACE MEASUREMENT OF CO, CH4, AND CO2 IN HIGH PURITY GASES BY GC-FID-METHANIZER: METHOD VALIDATION AND UNCERTAINTY ESTIMATION - Harry Budiman; Oman Zuas (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
In this study, method validation and uncertainty estimation for the measurement of trace amounts gas impurities such as carbon monoxide (CO), methane (CH4), and carbon dioxide (CO2) using gas chromatography flame ionization detector with methanizer (GC-FID-methanizer) are reported. The method validation was performed by investigating the following performance parameters such as selectivity, limit of detection (LOD), limit of quantification (LOQ), precision, linearity, accuracy, and robustness. The measurement uncertainty to indicate the degree of confidence of the analytical results was estimated by using a bottom up approach. The results reveals that the method possess good repeatability (% relative standard deviation RSD < 1 %) and intermediate precision (RSD % < 5 %) properties for the measurement of trace level CO, CH4, and CO2. No bias was found for the validated method. The linearity of the method was found to be remarkable with correlation coefficient (R2) higher than 0.995 for all target analytes. In addition, the measurement uncertainty of the CO, and CO2 in high purity helium (He) gas sample measured using the validated method were found to be 0.08 µmol∙mol-1, and 0.11 µmol∙mol-1, respectively, at 95 % of confidence level. No measurement uncertainty was obtained for CH4 in high purity gas sample due to its concentration was below the GC-FID-methanizer detection level. In conclusion, the GC-FID-methanizer under experimental condition of this study is reliable and fit for the measurement of trace levels of CO, CH4 and CO2 in high purity gas samples.